The Origins and Agency of the Miraculous Annunciation at the Santissima Annunziata in Counter-Reformation Florence - Stowell, Steven F. H. (Renaissance and Reformation / Renaissance et Réforme, 2022)
Research on miracle-working images has shown that devotees attributed their power to the authentic likeness of the holy people these images possessed. An authentic likenss of Christ, for instance, possessed his seemingly infinite agency. Using the miraculous painting of the Annunciation at the Santissima (SS.) Annunziata in Florence as a case study, this article questions whether an image’s agency was indeed limitless. Based on an examination of various hagiographical writings on the shrine written during the Counter-Reformation period, in particular Angelo Lottini’s Scelta d’alcuni miracoli e grazie della Santissima Nunziata di Firenze, this article proposes that certain miracles were connected with the image’s origins. In light of James Frazer’s theory of sympathetic magic, and Alfred Gell’s more recent theory of art and agency, this article argues that these post-Tridentine writings define the Annunziata image’s agency by the circumstances of its origins, which made it especially (though not exclusively) powerful over problems relating directly or conceptually to the mind, imagination, and eyes.